Gas Sensing of (SnO2)1-x(ZnO)x Composite Associating with Electrical Properties - Yas, Dunia (Iraqi Journal of Physics, 2019)
Abstract Semiconductor-based gas sensors were prepared, that use n-type tin oxide (SnO2) and tin oxide: zinc oxide composite (SnO2)1-x(ZnO)x at different x ratios using pulse laser deposition at room temperature. The prepared thin films were examined to reach the optimum conditions for gas sensing applications, namely X-ray diffraction, Hall effect measurements, and direct current conductivity. It was found that the optimum crystallinity and maximum electron density, corresponding to the minimum charge carrier mobility, appeared at 10% ZnO ratio. This ratio appeared has the optimum NO2 gas sensitivity for 5% gas concentration at 300 °C working temperature.